Improving Guideline-Congruent Care for Chemotherapy-Induced Nausea and Vomiting Prophylaxis in Pediatric Oncology Patients. Issue 3 (March 2022) - Diorio, Caroline; Vardaro, Julie; Wei, Yahui; Mauro, Jane; Croy, Colleen; Oranges, Katelyn E.; Flanagan, Lindsay; Reilly, Anne F.; Bailey, L. Charles; Jubelirer, Tracey; Elgarten, Caitlin W.; Freedman, Jason L.
Abstract : PURPOSE: Chemotherapy-induced nausea and vomiting (CINV) is a very common side effect of pediatric cancer therapy. High-quality, evidence-based, pediatric-specific guidelines for prophylaxis and treatment of CINV are available. At many centers, guideline-concordant care is uncommon. We formed a multidisciplinary quality improvement team to implement guideline-concordant care for CINV prophylaxis at our center. We present the results following the first year of our interventions. METHODS: We planned and implemented a multipronged approach in three key phases: (1) developing and publishing an acute CINV prophylaxis pathway, (2) education of providers, and (3) updating the computerized provider order entry system. We used iterative, sequential Plan-Do-Study-Act cycles and behavioral economic strategies to improve adherence to guideline-concordant CINV prophylaxis. We focused on aprepitant usage as a key area for improvement. RESULTS: At the beginning of the study period, < 50% of patients were receiving guideline-concordant CINV prophylaxis and < 15% of eligible patients were receiving aprepitant. After 1 year, more than 60% of patients were receiving guideline-concordant care and 50% of eligible patients were receiving aprepitant. CONCLUSION: We describe the development and implementation of a standardized pathway for prevention of acute CINV in pediatric oncology patients. With a multidisciplinary, multifaceted approach, we demonstrate significant improvements to guideline-congruent CINV prophylaxis.